Coefficients of a Comprehensive Subclass of Meromorphic Bi-Univalent Functions Associated with the Faber Polynomial Expansion - Hari Mohan Srivastava; Ahmad Motamednezhad; Safa Salehian (Axioms, 2021)
In this paper, we introduce a new comprehensive subclass <semantics>ΣB(λ,μ,β)</semantics> of meromorphic bi-univalent functions in the open unit disk <semantics>U</semantics>. We also find the upper bounds for the initial Taylor-Maclaurin coefficients <semantics>|b0|</semantics>, <semantics>|b1|</semantics> and <semantics>|b2|</semantics> for functions in this comprehensive subclass. Moreover, we obtain estimates for the general coefficients <semantics>|bn|<mspace width="0.277778em"></mspace>(n≧1)</semantics> for functions in the subclass <semantics>ΣB(λ,μ,β)</semantics> by making use of the Faber polynomial expansion method. The results presented in this paper would generalize and improve several recent works on the subject.